2010
DOI: 10.1371/journal.pone.0010891
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Endocannabinoids, Astrocytes and p38 Phosphorylation in the Resolution of Postoperative Pain

Abstract: BackgroundAn alarming portion of patients develop persistent or chronic pain following surgical procedures, but the mechanisms underlying the transition from acute to chronic pain states are not fully understood. In general, endocannabinoids (ECBs) inhibit nociceptive processing by stimulating cannabinoid receptors type 1 (CB1) and type 2 (CB2). We have previously shown that intrathecal administration of a CB2 receptor agonist reverses both surgical incision-induced behavioral hypersensitivity and associated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 57 publications
(83 reference statements)
2
60
0
Order By: Relevance
“…This model, in which a surgical incision in the animal’s hind paw causes thermal and tactile hypersensitivity, displays similarities to the human postoperative pain syndrome and relies on CaV2.2 for pain signal transmission. 17 Mechanistically, p38, a Cdk5 substrate, 77 is hyperphosphorylated in DRG during postsurgical pain, 2 reflecting increased Cdk5 activity. We reported that Cdk5-mediated CRMP2 phosphorylation increases its binding to CaV2.2, which augments calcium influx 11 ; thus, the increased interaction between CRMP2 and CaV2.2 may underlie the mechanism of antinociception in this particular model.…”
Section: Discussionmentioning
confidence: 99%
“…This model, in which a surgical incision in the animal’s hind paw causes thermal and tactile hypersensitivity, displays similarities to the human postoperative pain syndrome and relies on CaV2.2 for pain signal transmission. 17 Mechanistically, p38, a Cdk5 substrate, 77 is hyperphosphorylated in DRG during postsurgical pain, 2 reflecting increased Cdk5 activity. We reported that Cdk5-mediated CRMP2 phosphorylation increases its binding to CaV2.2, which augments calcium influx 11 ; thus, the increased interaction between CRMP2 and CaV2.2 may underlie the mechanism of antinociception in this particular model.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, overexpression of CB 2 receptors protected against nerve injury-induced thermal and mechanical allodynia and prevented glial activation in the spinal cord. Numerous other studies have also implicated EC signalling in glial cell activation (64,103,104) .…”
Section: Spinal Mechanismsmentioning
confidence: 97%
“…For example, conditional knockdown of neuropeptide tyrosine (NPY) before the initiation of inflammation extended the time course of mechanical and heat hyperalgesia (Solway et al, 2011). Similarly, dual blockade of cannabinoid CB1 and CB2 receptor signaling prevents the resolution of postoperative allodynia (Alkaitis et al, 2010). These studies indicate that endogenous NPY and endocannabinoids hasten the resolution of inflammatory and neuropathic pain.…”
Section: Opioid Receptors and Endogenous Analgesiamentioning
confidence: 99%
“…However, numerous receptor systems besides MOR likely maintain LS in remission, LS is masked not only by opioid receptor activity, but also by endocannabinoids (Alkaitis et al, 2010, Ji et al, 2011), alpha-2 adrenergic receptors (De Felice et al, 2011), and neuropeptide Y (NPY) receptor activity (Solway et al, 2011). For example, our lab recently used conditional NPY knockout mice and NPY Y1 and Y2 receptor antagonists to demonstrate that the endogenous NPY system in the DH is involved in repressing the LS induced by inflammation or nerve damage (Solway et al, 2011).…”
Section: Opioid Receptor-masked Sensitizationmentioning
confidence: 99%